La cooperación triangular México-Japón - Uscanga, Carlos (Revista Española de Desarrollo y Cooperación, 2023)
Triangular Cooperation between Mexico and Japan is an innovative modality in their international strategies. This has generated new areas of work where the Mexican government may have the opportunity to reintegrate back, under the collaboration with Tokyo, as a major player in Latin America within the regional system of cooperation and strengthening, at the same time, bilateral ties with Japan as strategic partners.